Cripto stabilizes GRP78 on the cell membrane. (27th December 2017) - Kouznetsova, Valentina L.; Hu, Hannah; Teigen, Knut; Zanetti, Maurizio; Tsigelny, Igor F.
Abstract: The ER resident chaperone molecule GRP78 has been shown to translocate to the cell surface where it associates with Cripto and signals cell growth, playing a still partially understood role in tumorigenesis. Consequently, a better understanding of GRP78 topology and structure at the surface of cancer cells represents an important step in the development of a new class of therapeutics. Here, we used a set of programs for creation of a complex containing GRP78 and Cripto proteins. We elucidated possible interactions of GRP78, Cripto, and their complex with the membrane. Using molecular dynamics simulations, we demonstrated that Cripto binding to GRP78 completely changes the dynamics of its behavior on the membrane, not allowing GRP78 to disconnect from it, thus enabling GRP78 tumorigenic functions.